Distância da Antena e Potência Absorvida na Cabeça do Usuário de Telefone Celular Portátil 10.14209/jcis.2001.3 - A. de Salles, Álvaro; Fernández, Claudio; Bonadiman, Mateus (Journal of Communication and Information Systems, 2015)
The development of a software to estimate the Specific Absorption Rate (SAR) in the head and in the eyes of portable transmitters (such as cellular phones) user’s employing the finite difference time domain (FDTD) method is shown in this work. The relevant results obtained with this model are compared with those estimated and measured by other authors. Alternatives aiming to reduce health risks are discussed, including the use of antennas radiating energy away from the user’s head.